Assessment of maternity knowledge and evaluation of obstacles to successful breastfeeding - Savić, Nikola; Milošević , Marijana; Mladenović, Marija; Jokić , Zoran; Anđelić, Slađana (Halo 194 Scientific Journal of Emergency Medicine, 2021)
Introduction: A healthy diet is a prerequisite for a child’s health. Aim: To examine the knowledge of mothers about the importance of breastfeeding, to evaluate obstacles to successful breastfeeding. Methods: The first part of the research is designed as a cross-sectional study. A questionnaire for mothers was constructed to assess their level of awareness of the importance of breastfeeding, the second part of the research includes a telephone survey, regarding the presence of obstacles to successful breastfeeding. Results: Descriptive statistics methods were used in the analysis. The largest number of women are aged between 21 and 25 (57%), 88% of children at birth received a grade of 9, 78% of women started breastfeeding the next day. After 7 days of discharge from the hospital, 7% of women did not breastfeed. Conclusion: The results of the research indicate the need for a greater degree of education of mothers about breastfeeding.